Exploring and evaluating differentiated assessment practices of in-service teachers for components of differentiation - Kaur, Amrita (Routledge, 2018)
Classroom assessment is central to effective teaching and learning, making assessment literacy a core component for teacher education.The present study explores self-reported, differentiated assessment practices of Malaysian in-service teachers.The practices were evaluated using an analytic framework that was developed based upon the existing literature on components of differentiation.Data were collected from 32 in-service teachers using open-ended survey questionnaires.Twelve of the teachers also participated in in-depth interviews.Documents provided by the teachers were also analyzed. Data from the open-ended survey were analyzed using NVivo11 to develop codes for the analytic framework.The findings offer insights into teachers’ knowledge, application, and interpretation of differentiated assessment practices.The discussion explores teachers’ explanations of their own practices and, further, recommends ways to improve knowledge and application of differentiated assessment.The implications of the findings are discussed for assessment literacy-related professional development for teachers, school management and policies to facilitate implementation of differentiated assessment.